Marketing Strategy of NOVA Employment - Liang, Yubo (International Journal of Global Economics and Management, 2024)
This paper targets identifying challenges faced by the Australian non-profit organization NOVA in providing more suitable job opportunities for disabilities, focusing on communication barriers between NOVA and decision-makers in Small and Medium Enterprises (SMEs). It discusses how NOVA improve its competitiveness by providing unique services through market segmentation, targeting, differentiation, and positioning (STDP) strategies. This paper also emphasizes the current situation for disabilities of finding jobs and explores leveraging LinkedIn to achieve SMART goals, including showcasing services, expanding networks, and using LinkedIn tools to attract target audience.